2018
DOI: 10.5194/acp-18-16099-2018
|View full text |Cite
|
Sign up to set email alerts
|

Is there an aerosol signature of chemical cloud processing?

Abstract: Abstract. The formation of sulfate and secondary organic aerosol mass in the aqueous phase (aqSOA) of cloud and fog droplets can significantly contribute to ambient aerosol mass. While tracer compounds give evidence that aqueous-phase processing occurred, they do not reveal the extent to which particle properties have been modified in terms of mass, chemical composition, hygroscopicity, and oxidation state. We analyze data from several field experiments and model studies for six air mass types (urban, biogenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 118 publications
1
41
0
Order By: Relevance
“…Schum et al () showed that the oxygen‐to‐carbon (O:C) ratio for wildfire‐influenced aerosols (~0.45–0.48) transported over 7–10 days in the free troposphere to the PICO Mountain Observatory in the North Atlantic was lower compared to that of North American outflow aerosols transported mainly through the MBL over only three days (~0.57). While the O:C ratio difference was attributed to the free tropospheric particles being more viscous and thus less vulnerable to oxidation than the MBL aerosols, it is worth considering in future model‐measurement studies how enhanced humidity and cloudiness in the WNAO MBL could enhance the O:C ratio via aqueous oxidation pathways (Ervens et al, ; Ervens et al, ). Further, it is unclear as to what the vertical and spatial profile is of brown carbon over the WNAO and how those profiles are impacted by humidity and clouds.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Schum et al () showed that the oxygen‐to‐carbon (O:C) ratio for wildfire‐influenced aerosols (~0.45–0.48) transported over 7–10 days in the free troposphere to the PICO Mountain Observatory in the North Atlantic was lower compared to that of North American outflow aerosols transported mainly through the MBL over only three days (~0.57). While the O:C ratio difference was attributed to the free tropospheric particles being more viscous and thus less vulnerable to oxidation than the MBL aerosols, it is worth considering in future model‐measurement studies how enhanced humidity and cloudiness in the WNAO MBL could enhance the O:C ratio via aqueous oxidation pathways (Ervens et al, ; Ervens et al, ). Further, it is unclear as to what the vertical and spatial profile is of brown carbon over the WNAO and how those profiles are impacted by humidity and clouds.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Due to a lack of observations of IEPOX SOA tracers in cloudwater and the high variability of liquid water content and pH in both the aerosol and cloud phases, the percentage of IEPOX SOA produced in cloudwater and aqueous aerosol remains unclear [11,38,56]. The observed lack of correlation between SOA mass and several aerosol properties, including liquid water content and pH, for ambient data may also be clarified by considering production in clouds [57].…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Although the composition of aqueous aerosols can vary considerably, liquid water and aqueous organic material are a significant portion of atmospheric aerosol mass [7][8][9], and much of the aqueous-phase organic material that comprises aerosols is known to be secondary. The cycling between aqueous aerosols and cloudwater provides two different aqueous environments in which aqueous secondary organic aerosol material (aqSOA) can form [10,11]. Since both environments are aqueous, the same chemical processes occur in both environments.…”
Section: Introductionmentioning
confidence: 99%
“…2a and S2), the overall signal of organic aerosol is much stronger in these two sets, such that the absolute concentration of oxalate (MO7: 0.47 µg m −3 ; MO8: 0.42 µg m −3 ) is still greater than in MO12 (0.19 µg m −3 ) and MO14 (0.37 µg m −3 ). However, biomass burning is a welldocumented source of both oxalate and longer-chain dicarboxylic acids (e.g., Falkovich et al, 2005;Nirmalkar et al, 2015;Cheng et al, 2017;Deshmukh et al, 2018;Thepnuan et al, 2019).…”
Section: Variability Of Water-soluble Organic Speciesmentioning
confidence: 99%
“…Succinate has been linked to biomass burning emissions (Wang and Shooter, 2004;Falkovich et al, 2005;Zhao et al, 2014;Balla et al, 2018), vehicular emissions (Kawamura andKaplan, 1987;Kawamura et al, 1996;Yao et al, 2004), and secondary production via photochemical reactions of precursor organic compounds (Kawamura and Ikushima, 1993;Kawamura et al, 1996;Kawamura and Sakaguchi, 1999). The two MO MOUDI sets thought to have the most influence from biomass burning emissions (MO7 and MO8) had the highest organic aerosol mass concentrations and the highest mass percent contributions of succinate to the organic aerosol (MO7: 14.3 % and MO8: 17.5 %).…”
Section: Variability Of Water-soluble Organic Speciesmentioning
confidence: 99%